Predictive Roles of Thinking Styles in Coping Strategies Among Mainland Postgraduate Students in Hong Kong - Chen, Siyao (Frontiers in Psychology, 2022)
The primary objective of the present research was to explore the statistical predictive power of thinking styles in coping strategies beyond demographic factors. One hundred and forty-eight mainland postgraduate students were administered to the Thinking Styles Inventory-Revised II (TSI-R2) and the Coping Orientation to Problems Experienced (COPE) Revised. Results indicated that Type I thinking styles primarily predicted adaptive coping strategies, while Type II thinking styles positively contributed to maladaptive coping strategies. Results in the present research were largely in the expected directions beyond the influence of demographic factors. Furthermore, thinking styles varied as a function of age, gender, gender-role orientation, and marital status. Implications for postgraduate students, academics, university administrators, and the limitations of the research, are discussed.